PENGEMBANGAN UMKM KULINER MELALUI PENDEKATAN BISNIS MODEL INOVASI (BMI) KOTA BOGOR - Vera Clara Simanjuntak; Dadang Junaedi; Dadi Muhamad Hasan Basri (Institut Teknologi dan Bisnis Dewantara, 2025)
This study aims to understand the Development of Culinary SMEs through a Business Model Innovation (BMI) approach in Bogor City. The population used in this study consists of all culinary SMEs located in Bogor City. The research location is in Bogor City, covering 5 districts, with samples taken from each district. This study is an associative causal research using a quantitative approach, with a sample of 100 respondents. The analysis technique used in this study is multiple linear regression analysis using SPSS 26. The test results show that business model resources have a positive and significant effect on business model policy in SMEs in Bogor City. Business model resources have a positive and significant effect on innovation in SMEs in Bogor City. Business model strategy has a positive and significant effect on business model policy in SMEs in Bogor City. Business model strategy has a positive and significant effect on innovation in SMEs in Bogor City. Innovation has a positive and significant effect on performance in SMEs in Bogor City. Business model policies have a positive and significant effect on performance in SMEs in Bogor City.